2017
DOI: 10.1007/s12250-017-4048-x
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-zoster virus ORF7 interacts with ORF53 and plays a role in its trans-Golgi network localization

Abstract: Varicella-zoster virus (VZV) is a neurotropic alphaherpesvirus that causes chickenpox andshingles. ORF7 is an important virulence determinant of VZV in both human skin and nerve tissues, however, its specific function and involved molecular mechanism in VZV pathogenesis remain largely elusive. Previous yeast two-hybrid studies on intraviral protein-protein interaction network in herpesviruses have revealed that VZV ORF7 may interact with ORF53, which is a virtually unstudied but essential viral protein. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Recruitment of the second copy of pUL51 to the pUL7:pUL51 complex in solution requires pUL51 residues 8-40 ( Fig. 1 and S3), consistent with observations that the equivalent N-terminal region of the HCMV pUL51 homologue pUL71 is required for its self-association both in vitro and in cultured cells (28), and that VZV pUL51 homologue pORF7 can also form higher-order oligomers (12).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recruitment of the second copy of pUL51 to the pUL7:pUL51 complex in solution requires pUL51 residues 8-40 ( Fig. 1 and S3), consistent with observations that the equivalent N-terminal region of the HCMV pUL51 homologue pUL71 is required for its self-association both in vitro and in cultured cells (28), and that VZV pUL51 homologue pORF7 can also form higher-order oligomers (12).…”
Section: Discussionsupporting
confidence: 85%
“…Similar results have been observed in other α-herpesviruses. pORF53 and pORF7, the pUL7 and pUL51 homologues from varicella-zoster virus (VZV), co-localize with trans-Golgi markers in infected cells (11,12) and deletion of pORF7 causes a defect in cytoplasmic envelopment (13). Similarly, deletion of pUL7 or pUL51 from pseudorabies virus (PrV) causes defects in virus replication and the accumulation of cytoplasmic unenveloped virions (14,15), and PrV pUL51 co-localizes with Golgi membranes during infection (14).…”
Section: Main Text Introductionmentioning
confidence: 99%
“…5b-d), the VZV SCP is probably involved in functional interactions with other viral or host factors. Indeed, previous yeast two-hybrid studies have shown that VZV SCP interacts with components of the nuclear egress complex, including pORF24 and pORF27 (homologues of pUL34 and pUL31 of HSV-1, respectively), as well as the tegument proteins pORF7, pORF9 and pORF21 (homologues of pUL51, VP22 and pUL37 of HSV-1, respectively) [53][54][55] . These findings suggest possible alternative roles for SCP in the nuclear egress and secondary envelopment of VZV particles.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pORF7 seems to work in conjunction with other viral or cellular proteins and acts as an essential part to regulate cell-to-cell fusion and secondary envelopment of VZV virus particles in infected human skin and neurons. Previously, we found that pORF7 interacts with pORF53 and they co-localize in the trans-Golgi network (TGN) in VZV-infected cells [ 46 ]. Most recently, the structure of pUL51 in complex with pUL7, the pORF7 and pORF53 homologues from herpes simplex virus-1 (HSV-1), has suggested a conserved role for pORF7 and its homologues in promoting membrane scission during cytoplasmic envelopment of nascent virions [ 47 ].…”
Section: Future Directionsmentioning
confidence: 99%